A Case of Horner's Syndrome following Ultrasound-Guided Infraclavicular Brachial Plexus Block. (22nd August 2012) - Walid, Trabelsi; Mondher, Belhaj Amor; Mohamed Anis, Lebbi; Mustapha, Ferjani
Abstract : Horner's syndrome results from paralysis of the ipsilateral sympathetic cervical chain (stellate ganglion) caused by surgery, drugs (mainly high concentrations of local anesthetics), local compression (hematoma or tumor), or inadequate perioperative positioning of the patient. It occurs in 100% of the patients with an interscalene block of the brachial plexus and can also occur in patients with other types of supraclavicular blocks.In this case report, we presented a case of Horner's syndrome after performing an ultrasound-guided infraclavicular brachial plexus block with 15 mL of bupivacaine 0.5%. It appeared 40 minutes after the block with specific triad (ptosis, miosis, and exophtalmia) and quickly disappears within 2 hours and a half without any sequelae. Horner's syndrome may be described as an unpleasant side effect because it has no clinical consequences in itself. For this reason anesthesiologists should be aware of this syndrome, and if it occurs patients should be reassured and monitored closely.